WORK ANALYSIS OF HYDRAULIC STATIC PILE DRIVER EQUIPMENT ON PILE FOUNDATION WORK IN TERMS OF TIME AND COST - Abnu Azhar; Eliatun Eliatun (CERUCUK, 2022)
To make a building requires a strong foundation to withstand the load on it. the Physical Work Project, Renovation and Expansion of the District Court Building requires heavy equipment management in the form of piles, the piling method used is the Hydraulic Static Pile Driver. The pile management is needed to find out the estimated working time on the entire building so that the implementation goes according to or does not exceed the planned project time. Therefore, it is necessary to analyze the efficiency of the piling tool. The results of the descriptive analysis in this study obtained the production value of the Hydraulic Static Pile Driver tool. The highest production value was 0.23 meters/minute, and the lowest value was 0.21 meters/minute. The time required to complete the project erection work based on the planning is nine weeks, while the realization in the field to complete it in seven weeks. The planned implementation cost to complete the erection work for this project is Rp. 2,073,360,000. Meanwhile, the cost of field realization is Rp. 2,481,150,000. this means that the implementation costs in the field are greater than the planning costs of Rp. 407,790,000 this was due to the addition of 828.00 m3 of pile procurement volume and 828 m3 of piling and handling work, and 138 nos of pile connections.